Penanganan dan Pemulihan Konflik Sosial dalam Unjuk Rasa Besar Berdasarkan Undang-Undang Nomor 7 Tahun 2012 - Syarifuddin, Ammar (Journal of Contemporary Law Studies, 2026)
This study aims to analyze the mechanisms for preventing and managing social conflict during large-scale demonstrations under Law No. 7 of 2012 concerning Social Conflict Management, as well as to examine the role of the Indonesian National Police (Polri) in post-conflict recovery efforts. The research applies a normative legal method using statutory and conceptual approaches. The study is supported by primary, secondary, and tertiary legal materials collected through library research and analyzed qualitatively. The findings demonstrate that Law No. 7 of 2012 provides a comprehensive framework for social conflict management through preventive, responsive, and restorative mechanisms, including conflict prevention, conflict termination, reconciliation, rehabilitation, and reconstruction. In the context of large-scale demonstrations, the police hold a strategic role in maintaining public order, preventing escalation, facilitating mediation, and implementing post-conflict recovery measures. Nevertheless, the implementation of the law still encounters several challenges, including normative overlap with Law No. 9 of 1998 concerning Freedom of Expression in Public, inconsistent law enforcement practices, and the potential misuse of discretionary authority by state officials. Therefore, stronger regulatory harmonization, institutional supervision, and accountability mechanisms are necessary to ensure balanced protection between public order and democratic freedoms.